Antihypertensive drug use and risk of cognitive decline in the very old: an observational study – The Newcastle 85+ Study. Issue 10 (October 2015) - Peters, Ruth; Collerton, Joanna; Granic, Antoneta; Davies, Karen; Kirkwood, Thomas; Jagger, Carol
Abstract : Objectives: Older adults are a fast growing group in society and are at high risk of hypertension, cognitive decline and dementia. Antihypertensive drugs, particularly calcium channel blockers (CCB), have been associated with a decreased risk of cognitive decline and dementia. We used observational data to examine the association between antihypertensive drug class and change in cognitive function. Methods: The Newcastle 85+ Study is a population-based cohort study recruiting individuals aged 85 (born in 1921) via general/family practices in Newcastle/North Tyneside, United Kingdom. Data, including blood pressure, antihypertensive drug use and cognitive function [assessed using the Standardized Mini-Mental State Exam (SMMSE)], were collected at baseline and 3-year follow-up. Results: The study population comprised 238 participants with a diagnosis of hypertension, prescribed antihypertensive drug treatment and with baseline and follow-up SMMSE assessment. There was an association between CCB use and less cognitive decline over 3 years (rate of decline was lower by 1.29 SMMSE points (95% confidence interval 0.16–2.42; P = 0.03) compared with those taking other antihypertensive classes after adjustment for age, sex, years of education, baseline SMMSE score, smoking, BMI, baseline blood pressure, and incident cerebrovascular event. This finding was even stronger in the cognitively intact (SMMSE >24), wherein rate of cognitive decline was lower by 1.33 SMMSE points (95% confidence interval 0.30–2.37; P = 0.01), but was not seen for other antihypertensive classes. Conclusion: Findings provide support for an association between CCB use and a lower rate of cognitive decline in very old adults with hypertension.